Pembiasaan Shalat Jamaah Dalam Membentuk Kemandirian Santri di Pondok Pesantren Darussalam Subah Batang - Khayatul Mustaqimah; Ngarifin Shidiq; Ahmad Robihan (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
This study aims to describe the implementation of congregational prayer and its role in fostering student independence at the Darussalam Subah Batang Islamic Boarding School. The study employed a qualitative approach with field research. The data sources consisted of primary data obtained through interviews with caretakers, administrators, and students, as well as secondary data obtained from documents and various relevant literature. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Data validity was tested using source triangulation and technical triangulation. The results indicate that congregational prayer at the Darussalam Subah Batang Islamic Boarding School is practiced routinely during the five obligatory prayer times and is a mandatory activity for all students. This practice plays a role in fostering student independence, demonstrated by the growth of discipline, responsibility, time management skills, self-control, and an awareness of worship without constant command or supervision. The success of the habit of congregational prayer in fostering student independence is supported by clear Islamic boarding school regulations, exemplary behavior from the caretakers, the active role of the administrators, a religious environment, consistent implementation of the habit, peer support, student self-awareness, and adequate facilities and infrastructure. Thus, the habit of congregational prayer contributes significantly to fostering student independence at the Darussalam Subah Batang Islamic Boarding School.